Body fat percentage and Body Mass Index in association with menstrual irregularities in young adults: A cross-sectional study - de Liyis, Bryan Gervais; David, George; Gunawan, Made Favian Budi (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS 1. Body fat percentage and BMI were found to be associated with menstrual cycle and menstrual bleeding period.2. The odds of having a prolonged menstrual cycle were increased by a factor of 1.109 with an increase of one unit of body fat percentage, while the odds of having a prolonged menstrual bleeding period was decreased by a factor 0.887 with an increase of one unit of body fat percentage.   ABSTRACT Objectives: Body fat percentage measures overall amount of fat as a proportion of total body weight. Basal metabolic index (BMI) is an unreliable predictor of body fat percentage as excess fat, lean, muscle, or bone density are indifferentiable. However, the relation between body fat percentage and BMI on menstrual characteristics are still unclear. The aim was to compare the correlations between body fat percentage and BMI towards menstrual characteristics.Materials and Methods: A cross-sectional sample of 211 young adults was taken by means of cluster random sampling. Cross tabulations were performed between variables and Pearson's chi square value were observed. Multiple logistic regressions were performed to observe the odds ratio and 95% confidence interval.Results: Body fat percentage was found to be associated with menstrual cycle (p=0.000) and menstrual bleeding period (p=0.000) but not daily pads usage, intermenstrual bleeding, and menstrual pains. Age was found not to correlate with any of the collected menstrual characteristic data. BMI was also found to be associated with menstrual cycle (p=0.008) and menstrual bleeding period (p=0.003). Further analysis showed that a one unit increase of body fat percentage was linearly correlated with increased of menstrual cycle by a factor of 1.109 days (p<0.01) and a decreased of menstrual bleeding period by a factor of 0.887 days (p<0.01).Conclusion: Although both body fat percentage and BMI showed associations with menstrual cycle and menstrual bleeding period, only body fat percentage was linearly correlated with menstrual cycle and menstrual bleeding period.